2017
DOI: 10.1055/s-0037-1603200
|View full text |Cite
|
Sign up to set email alerts
|

Open Carpal Tunnel Release Outcomes: Performed Wide Awake versus with Sedation

Abstract: Carpal tunnel release (CTR) is the most common surgery of the hand, and interest is growing in performing it under local anesthesia without tourniquet. To better understand differences, we hypothesized that patients undergoing CTR under wide-awake local anesthesia with no tourniquet (WALANT) versus sedation (monitored anesthesia care [MAC]) would not result in a difference in outcome. Consecutive cases of electrodiagnostically confirmed open CTR across multiple surgeons at a single center were prospectively en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Postoperative VAS scores in group WA were significantly lower during the immediate postoperative period. Tulipan et al reported that there was no difference in VAS scores at 2 weeks and 3 months after surgery when WA and sedation were compared as an anesthetic method of CTS 13. However, this study did not address immediate postoperative pain.…”
Section: Discussionmentioning
confidence: 84%
“…Postoperative VAS scores in group WA were significantly lower during the immediate postoperative period. Tulipan et al reported that there was no difference in VAS scores at 2 weeks and 3 months after surgery when WA and sedation were compared as an anesthetic method of CTS 13. However, this study did not address immediate postoperative pain.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the WALANT technique can be used in patients who are at a risk of adverse effects from general anesthesia. This technique has been used in various operations in orthopedic surgery, such as distal radius fracture, ulnar shaft fracture, and olecranon fracture [ [2] , [3] , [4] , [5] ]. However, its use has not yet been reported in a mid-shaft clavicular fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Wide-awake local anesthesia no tourniquet (WALANT) has been widely used in orthopedic surgery [ [2] , [3] , [4] , [5] ]. However, there have been no reports of its use in clavicular surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Carpal tunnel release is performed as an outpatient procedure and thus, the demand of earlier discharge and increased efficiency has led to consideration of alternative anesthesia techniques than sedation (monitored anesthesia care [MAC]). 1 Wide awake carpal tunnel surgery provides significant cost saving with almost the same patients’ satisfaction as sedation anesthesia. 8 9 10 Several regional anesthesia techniques, such as brachial plexus blocks, 11 12 intravenous regional anesthesia, 13 wrist blocks, 14 15 and local infiltration 14 15 16 17 have been introduced.…”
Section: Discussionmentioning
confidence: 99%
“…It may be performed under wide awake local anesthesia and is well tolerated by the patients. 1 Besides, superficial infiltration of the local anesthetic provides adequate intraoperative analgesia. 2 The advantage of using local anesthesia in such surgical procedures is that it allows a rapid turnover of patients and avoids the complications of regional and general anesthesia.…”
Section: Introductionmentioning
confidence: 99%